Comparing Revision Total Knee Arthroplasty Stems at a High-Volume Revision Center - Kemker, Bernard P.; Sowers, Christopher B.; Seedat, Raees; Satpathy, Jibanananda; Patel, Nirav K.; Lombardo, Daniel J.; Golladay, Gregory J. (Frontiers in Surgery, 2022)
Introduction Hybrid fixation and fully cemented fixation are commonly used in revision total knee arthroplasty (rTKA). These two techniques are typically done based on surgeon preference and one has not demonstrated superiority over the other. The purpose of this study was to examine if there was a difference in survivorship between the two different techniques. Methods A retrospective cohort study of all consecutive patients undergoing rTKA (CPT 27487) from January 1, 2011 to January 1, 2018 at a single academic center was performed. Patients were divided into cemented and hybrid rTKA groups with comparison of patient demographic, clinical and radiological outcomes, reoperation, change in post-operative hemoglobin (HgB), and length of stay (LOS). Results A total of 133 rTKA for 122 patients were identified: 30.1% in the cemented and 69.9% in the hybrid groups. There was no significant difference in age (p=0.491), sex (p=0.250), laterality (p=0.421), or body mass index (BMI) (p=0.609) between the two groups. Mean LOS (hybrid 4.13 days, cemented 3.65 days; p=0.356) and change in Hgb (hybrid 2.95mg/dL, cemented 2.62mg/dL; p=0.181) were not statistically different between the groups. Mean follow up for the hybrid (25.4 months, range 2–114 months) and cemented (24.6 months, range 3–75.5 months) rTKA was not statistically significant (p=0.825). Overall survival rates were 80.9% in the hybrid and 84.6% in the cemented groups (p =0.642). Conclusions Hybrid and fully cemented rTKA techniques have similar survival rates at a minimum follow-up of 2 years. Additionally, in our cohort, age, gender, and BMI were not associated with failure in either group. Furthermore, we did not observe differences in LOS or change in hemoglobin suggesting early postoperative complications may not differ between cemented and hybrid stemmed groups. Continued long-term research is required for defining the best rTKA technique.